Application of GIS and Remote Sensing for Analyzing Agricultural Land Dynamics of Munshiganj Sadar, Bangladesh - Mollah, Tanjinul Hoque; Ferdous, Monalisha; Aunkur, Md. Masuk Mowla; S. M. Hozaifa; Rahman, Toufiqur; Kanij, Jannatul (The Jahangirnagar Review, 2025)
Agricultural land in Munshiganj Sadar has faced continuous pressure from urbanization, infrastructural growth, and population increase over the past two decades, resulting in notable transformations of the landscape. This study employs GIS and Remote Sensing technologies toanalyze land use and land cover (LULC) changes from 2004 to 2024 and predict future dynamics up to 2034. Findings reveal a substantial increase in cropland, with a 37.8% rise between 2014 and 2024, alongside a severe decline in waterbodies and minor forest loss. Probability matrix analyses indicate continued expansion of agriculture and urban areas, while river courses and aquatic zones show signs of environmental stress. Despite projected stability in agricultural land through 2034, the results highlight the urgent need for sustainable land management strategies. The integration of GIS and RS proves critical for monitoring spatial patterns and supporting informed decision-making for agricultural planning and ecological preservation in the region.